WEB DESIGN SMK NEGERI 1 LUBUK SIKAPING - RAHMANANDA ZULKARNAIN, Drs. Nasbahri Couto, M.Sn, Riri Trinanda, S.Pd., M.Sn (DEKAVE : Jurnal Desain Komunikasi Visual, 2014)
Vocational high school (SMK) isone ofthetop school sare regular directits graduates workingin the corporate world, the concept of SMK Negeri 1 Lubuk Sikaping is giving a special skill foreach student de pending . where learning done detail eddis cussio nofa to picto it’s conclusion, the website is expectedto support teaching and learning in SMK Negeri 1 Lubuk Sikaping because access to learn and inter actnotonly in school but al socan be doneat any time (online). In addition,the school website also helps disseminate information to the public about the SMK Negeri 1 Lubuk Sikaping There fore , to introduce and al so in form SMK Negeri 1 Lubuk Sikaping, promotional media design need seffectively and efficiently and have a broad range for SMK 1 Lubuk Sikaping such, sowillaim to intro duce school SMK Negeri 1 Lubuk Sikaping can beachievedto the target audience. For the design process begins with data collection, observation, interview and documentation. So the problem sthatoccur in SMK Negeri Lubuk Sikaping be known, from theidentification ofthe problem analyzed byusing the theory of SWOT (strenght /strengths, weakness/weakness, opportunity/opportunities, threat/threats), with the under standing theen tire information in acase.Keywords: SMKN 1 LubukSikaping, web design, Effective and efficient.